PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN SIKAP SPIRITUAL DAN SOSIAL SISWA KELAS I DI SDIT AR-RAHMAN SUKOHARJO - Setya Lingga Yanie; Rifatul Azizah; Fadhilah Khoirun Nisa; Tiara Putri; Muhammad Jauhari Muhsin; Satria Darul Ramadhan; Praptiningsih (Jurnal Binagogik, 2026)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in fostering the spiritual and social attitudes of first-grade students at SDIT Ar-Rahman Sukoharjo. A descriptive qualitative approach was employed, and data were collected through observation, interviews, and documentation. The findings indicate that PAI teachers not only deliver religious content but also shape students’ character through positive routines such as collective prayer and daily worship practices. PAI teachers act as educators, guides, and role models in instilling Islamic values including discipline, responsibility, and empathy. Through storytelling, questioning, and simulation activities, teachers create a conducive, enjoyable, and spiritually enriching learning atmosphere. The study concludes that the role of PAI teachers is essential in developing students’ religious and social character from an early age through warm and contextually relevant learning interactions.